1993
DOI: 10.1016/0014-5793(93)80741-c
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a novel cysteine/histidine‐rich metal binding domain from Xenopus nuclear factor XNF7

Abstract: A 42 amino acid synthetic peptide corresponding to a newly defined cysteitmkistidine-rich protein motif called B-box, from the Xenopur protein XNF7 has been character&d. The metal-binding stokhiometry and dissociation constant for zinc were determined by competition with the chromopho~c chelator Br,BAPTA, demons~ating that one zinc atom binds per molecule of peptide despite the presence of seven putative metal ligands, and represents the t&t application of this method to measuring zinc stoichiometry of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…Our previous work has shown that, although there are seven potential metal ligands, the XNF7 B-box peptide binds only one Zn2+ per molecule and the Zn2+ is bound tetrahedrally (24). Therefore, of the seven potential ligands conserved in XNF7 B-box (see Fig.…”
mentioning
confidence: 99%
“…Our previous work has shown that, although there are seven potential metal ligands, the XNF7 B-box peptide binds only one Zn2+ per molecule and the Zn2+ is bound tetrahedrally (24). Therefore, of the seven potential ligands conserved in XNF7 B-box (see Fig.…”
mentioning
confidence: 99%
“…Production of soluble B-box proteins is challenging from heterologous expression systems, such as in E. coli (12). We observed that soluble full-length AtBBX32 protein can be expressed by coupled transcription/translation in a wheat germ cell-free system.…”
Section: Resultsmentioning
confidence: 96%
“…The propensity for aggregation and precipitation makes B-box domains poor candidates for crystal structure studies (12). Although there is no plant B-box structure reported, several B-box structures from other species have been determined (34).…”
Section: N-terminal B-box Domain Of Atbbx32 Is Essential For the Bindmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this domain may provide further insight into the potential mechanism of action of HERF1. In addition to AFP and RFP, whose functions remain unknown, several other RBCC proteins contain an rfp domain: MID1, which is mutated in Opitz syndrome, an inherited human multiorgan disorder primarily affecting midline structures (31); three Xenopus nuclear proteins (xnf7, XL43, and XL75), which are involved in early development (3,30); and the amphibian PwA33 protein, which binds to nascent transcripts on lampbrush chromosome loops in oocytes (1). The rfp domain is also found associated with an immunoglobulin domain in butyrophilin, a secreted protein found in milk (13).…”
Section: Discussionmentioning
confidence: 99%